2008
DOI: 10.2337/dc08-0509
|View full text |Cite
|
Sign up to set email alerts
|

Is a Priming Dose of Insulin Necessary in a Low-Dose Insulin Protocol for the Treatment of Diabetic Ketoacidosis?

Abstract: OBJECTIVE—The purpose of this study was to assess the efficacy of an insulin priming dose with a continuous insulin infusion versus two continuous infusions without a priming dose. RESEARCH DESIGN AND METHODS—This prospective randomized protocol used three insulin therapy methods: 1) load group using a priming dose of 0.07 units of regular insulin per kg body weight followed by a dose of 0.07 unit · kg−1 · h−1 i.v. in 12 patients with diabetic ketoacidosis (DKA); 2) no load group using an infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 25 publications
1
74
1
6
Order By: Relevance
“…Although an initial bolus dose of 10 units regular insulin (0.1-0.15 units/ kg body weight) is recommended by most authors, 32,49 recent data from almost 200 DKA patients suggest this may confer no additional clinical benefit when the infusion dose is adequate (0.1-0.14 units/kg/hour for either DKA or HHS). 50,51 The administration rate should be increased by 50-100% if glucose does not fall ≥10% or 2.78 mmol/L (50 mg/dL) per hour, and decreased to 2-3 units/hour when glucose falls to 11.1 mmol/L (200 mg/dL) in DKA or 13.88 mmol/L (250 mg/dL) in HHS. 3,7 The serum glucose concentration should be maintained between 7.77-9.99 mmol/L (140-180 mg/dL) for ICU patients and between 5.55-9.99 mmol/L (100-180 mg/dL) for patients admitted to general medical wards.…”
Section: Insulin and Glucosementioning
confidence: 99%
“…Although an initial bolus dose of 10 units regular insulin (0.1-0.15 units/ kg body weight) is recommended by most authors, 32,49 recent data from almost 200 DKA patients suggest this may confer no additional clinical benefit when the infusion dose is adequate (0.1-0.14 units/kg/hour for either DKA or HHS). 50,51 The administration rate should be increased by 50-100% if glucose does not fall ≥10% or 2.78 mmol/L (50 mg/dL) per hour, and decreased to 2-3 units/hour when glucose falls to 11.1 mmol/L (200 mg/dL) in DKA or 13.88 mmol/L (250 mg/dL) in HHS. 3,7 The serum glucose concentration should be maintained between 7.77-9.99 mmol/L (140-180 mg/dL) for ICU patients and between 5.55-9.99 mmol/L (100-180 mg/dL) for patients admitted to general medical wards.…”
Section: Insulin and Glucosementioning
confidence: 99%
“…It has been demonstrated that a priming dose of insulin is not necessary, provided that the insulin infusion is started promptly at a dose of 0.14 unit kg )1 h )1 [33]. Although the insulin infusion ª 2011 The Authors.…”
Section: Use Of a Priming Dose (Bolus) Of Insulin?mentioning
confidence: 99%
“…Recently, a randomized trial has demonstrated that this "priming" bolus is unnecessary and that effective glycemic control can be achieved by starting the insulin drip at 0.14 U/kg per hour. 13 Glucose levels should decrease by 50 to 70 mg/dL per hour. If the serum glucose does not decrease by at least this value within the first hour, the insulin infusion rate should be doubled every hour until a steady decline is achieved.…”
Section: Insulin Therapymentioning
confidence: 99%